Successful salvage treatment of myxoid liposarcoma with multiple peritoneal seeding using helical tomotherapy-based intraperitoneal radiotherapy: a case report - Choi, Chihwan (BMC Res Notes, 2015)
BACKGROUND: Myxoid liposarcoma is the most common soft-tissue sarcoma that metastasizes to the peritoneal cavity. Recently, an advanced intensity-modulated radiotherapy, known as helical tomotherapy, has been introduced to improve target coverage, while reducing normal tissue radiation. Here, we report a case of myxoid liposarcoma with multiple peritoneal seeding that was chemotherapy-refractory, but was successfully salvaged by helical tomotherapy-based intraperitoneal radiotherapy. CASE PRESENTATION: A 71-year-old East-Asian male was initially diagnosed with myxoid liposarcoma in his left thigh by excision. Six years later, the patient underwent a left pneumonectomy for metastatic myxoid liposarcoma in the left lung. Since then, the patient was treated with two segmental resections, and multiple lines of chemotherapy, for repeated recurrences in the peritoneal cavity. The patient underwent intraperitoneal radiotherapy followed by tumor boost radiotherapy, as salvage treatment for chemotherapy-resistant metastatic peritoneal myxoid liposarcoma. The prescribed dose was 24 Gy delivered in 15 fractions of 1.6 Gy over 3 weeks, followed by a 16 Gy boost dose administered in eight fractions of 2 Gy, to multifocal peritoneal lesions. A positron emission tomography scan obtained 8 weeks after completion of radiotherapy, showed a complete metabolic response of metastatic peritoneal lesions. Radiotherapy was well tolerated, without any side effects. In a computed tomography scan obtained 20 weeks after completion of radiotherapy, most of the peritoneal metastatic lesions had disappeared, except for two small residual nodules. CONCLUSION: This case suggests that low fraction-sized intraperitoneal radiotherapy (1.6 Gy administered once daily), followed by a focal boost using helical tomotherapy, is a feasible treatment without side effects. It produced an excellent tumor response, and durable intraperitoneal control for metastatic peritoneal myxoid liposarcoma.